The ‘Great Imitator’: A Case of COVID-19 Presenting with Encephalitis and Acute Coronary Syndrome - Guntur Darmawan; Samadhi Tulus Makmud (Acta Medica Indonesiana)
Although typically patients with coronavirus disease-19 (COVID-19) have pulmonary symptoms atypical cases can occasionally present with extra-pulmonary symptoms. We report an interesting case of COVID-19 female patient presenting with combination of central nervous system disorder and acute myocardial infarct as initial manifestation. Multiorgan involvement in COVID-19 might lead to multiple atypical presentation which could be overlooked by the physician.